Implementation of Formative Assessment in Engineering Education - Sanchez-Lopez, Eva; Kasongo, Joseph; Gonzalez-Sanchez, Andres Filipe; Mostrady, Ahmed (Tecno Scientifica Publisher, 2023)
Formative assessment is an assessment of student learning that aims to improve students' skills or understanding of certain course themes. Formative evaluations are often conducted in class, can be conducted anonymously, and are typically much more focused on certain abilities or knowledge. This article presents a comprehensive literature analysis on formative assessment in engineering education. As an integrated narrative review, this study's methodology included a systematic search, review, and writing of the literature in order to synthesize the important themes and conclusions of research in this field. The authors selected and reviewed the available literature using qualitative thematic criteria, focusing on the relationship between formative assessment and students' attitudes, FA and self-regulation skills, online formative evaluation, validity, reliability, and dishonesty of assessment, and engagement with critical learning processes. An increase in student involvement and centrality in the process as primary actors, as well as the building of a learning community, are among the cited benefits. According to the primary results, effective online formative assessment can generate a student- and assessment-centered emphasis through formative feedback and enhanced learner engagement with significant learning experiences. In the context of online formative assessment, it has been discovered that ongoing authentic assessment activities and interactive formative feedback are vital for overcoming validity and reliability concerns.